1989
DOI: 10.1051/agro:19890903
|View full text |Cite
|
Sign up to set email alerts
|

Disposition des racines adventives autour de la tige de maïs (Zea mays L.)

Abstract: First, the root arrangement was studied on each internode considered separately. A x z test showed that roots were not arranged according to a random pattern (Table III). The assumption of a symmetrical arrangement has to be discarded too. On this assumption angles between roots would be equal to 360/1, I being the number of roots. This assumption could be accepted for I = 3 but could not be accepted for I = 2, or 1 = 4. For I = 3 the modal value of angles between roots was 120 degrees (Fig. 5). In this partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…The angle between roots was thus 27r/ni where ni is the number of roots on phytomer i. Radial angles of roots were shifted on successive phytomers in order to account for the alternating positions of roots (Pellerin et al, 1989). Insertion angles of roots (angle between the root and a vertical line) were randomly drawn from a normal distribution whose mean value and standard deviation were calculated from data published by Pellerin (1990, 1991).…”
Section: The Modelmentioning
confidence: 99%
“…The angle between roots was thus 27r/ni where ni is the number of roots on phytomer i. Radial angles of roots were shifted on successive phytomers in order to account for the alternating positions of roots (Pellerin et al, 1989). Insertion angles of roots (angle between the root and a vertical line) were randomly drawn from a normal distribution whose mean value and standard deviation were calculated from data published by Pellerin (1990, 1991).…”
Section: The Modelmentioning
confidence: 99%
“…A preliminary study (Pellerin et al, 1989) shows that although the arrangement of the primary roots is not defined through a regular phyllotaxis as that of the leaves is, they are not independently uniformly distributed. In particular the angular disposition of a randomly chosen root on an internode depends on the other roots of this internode and on the roots of the preceding internode.…”
Section: Introductionmentioning
confidence: 98%
“…Five internodes were observed which are denoted by I2±I6, following Girardin et al's (1986) notations, I2 being the ®rst observed internode. A preliminary study (Pellerin et al, 1989) shows that the roots are not independently uniformly distributed, in particular the angular location of a randomly chosen root on an internode depends on the locations of the other roots on this internode and on the locations of the roots on the preceding internode. Since the roots appear simultaneously on an internode and successively on the next internodes, we can assume that the locations on the internode i given the preceding internodes will depend only on the locations on the internode i À 1.…”
Section: Applicationmentioning
confidence: 99%
“…The interactions between roots were analysed using the theory developed above. The primary roots have an important physical effect on the stem stability (Pellerin et al, 1990) and also on the hydric and mineral nutrition (Pellerin et al, 1989) because they determine the root system. A complete description of the structure of maize plant can be found in Girardin et al (1986).…”
Section: Applicationmentioning
confidence: 99%